Optimization of Anthocyanins Extracts from Roselle (Hibiscus sabdarifa) Petals Using Ultrasonic-Assisted Extraction Method - Redzuan, S. (Springer Science and Business Media Deutschland GmbH, 2021)
Roselle petals contain high anthocyanins, a good antioxidant, and natural dark red colorants. Anthocyanins help in reducing risks of cardiovascular disease and colon cancer. But anthocyanins are easily affected by extraction process. Therefore, this study proposed a new method of extracting anthocyanins using ultrasonic-assisted extraction (UAE) from roselle petals with three extraction parameters. The extraction parameters are sampleâs particle size (0.125, 0.375 and 0.625Â mm), solvent to solid ratio (10:1, 15:1 and 20:1Â mL solvent/g solid) and extraction time (5, 10 and 15Â min). The optimization of process parameters aims to achieve the highest extraction yield of extract, Total Anthocyanins Content (TAC), and Antioxidant Activity (AA). The results show that 0.125Â mm of particle size, 10:1Â mL solvent/g solid, 15Â min of extraction obtained the best percent mass yield (64.72), TAC (70.97Â mg/L), and AA (90.05). Method-wise, this study showed that the ultrasonic-assisted extraction gives better quality of roselle petals extracts than the maceration extraction. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.